O PENSAMENTO GEOGRÁFICO E A LITERATURA INFANTIL: EXPLORAÇÕES A PARTIR DE PERCURSOS DIDÁTICOS ELABORADOS POR DOCENTES DOS ANOS INICIAIS DO ENSINO FUNDAMENTAL - Oliveira, Alex Soares de (2024)
This investigation is a participatory research, in a qualitative approach. The study was carried out at the Municipal School of Campo Rosa Zarpelon, located in Irati/Paraná. We use teaching materials created with teachers, we seek to analyze the potential and relationships between literature and geographic thinking in the early years of Elementary School. We intend to advance the understanding of the role of Geography and geographic thinking in the training of students and contribute to the development of pedagogical practices in the early years of Elementary School that consider the critical and well-founded presence of geographic knowledge. The preparation of data for this research took place in a participatory manner with three teachers working in the initial years. The teachers participated in two pedagogical workshops and chose a literary work to write a teaching resource based on the three dimensions of geographic thinking: structuring concepts, reasoning and geographic languages. Using these didactic paths, it was possible to verify that children's literature has the potential to be worked on in conjunction with the Geography subject as long as the content tradition of School Geography is overcome. Furthermore, it was found that the teachers completed all stages of the teaching path and developed classes based on the three dimensions of geographic thinking.